PENGARUH IMPLEMENTASI KEBIJAKAN ANGGARAN PENDAPATAN DAN BELANJA DESA TERHADAP KEBERHASILAN PEMBANGUNAN DI DESA KUSU LOVRA KECAMATAN KAO KABUPATEN HALMAHERA UTARA - NGANGANGOR, RISKY PAUL; POSUMAH, JOHNNY HANNY; SONDAKH, TELLY (JURNAL ADMINISTRASI PUBLIK, 2014)
ABSTRACT :This study questioned the fundamental problems, namely: the extent of theinfluence of policy implementation Budget Village (APBDes) the success of developmentin the village of Lovra Kusu District of North Halmahera Kao? Thus, this researchaims: to determine the extent of the effect of policy implementation Budget Village(APBDes), the success of Rural Development in Kusu Lovra Kao District of NorthHalmahera.This empirically using a quantitative approach to the application of descriptive andexplanatory methods. The data and information collected through questionnairesdistributed technique to 50 respondents, and is equipped with observation anddocumentation, then analyzed by applying techniques prosuct moment correlationanalysis and simple linear regression.Based on the results of data analysis, it is known that the success of the implementationAPBDes and Rural Development in the Rural District of Kao Kusu Lovra NorthHalmahera in the category "medium" or quite successful. This fact indicates that theoptimal policy implementation APBDes yet so can impact on non-optimal achievementof success of rural development in the village. This is due to inadequate availability ofresources, particularly the amount and quality of human resources involved in the policyitself APBDes.Thus, it can be concluded that the implementation of policy APBDes positive andsignificant impact on the success of rural development, particularly in rural Kusu LovraKao subdistrict of North Halmahera. To optimize the execution / implementation ofpolicies APBDes, North Halmahera district government needs to increase the numberand quality of village officials in charge of human resources managing rural financethrough professional technical training.Keywords : Implementation of policy, Budget Village, Rural Development.